Effectiveness of Hypnobirthing for Reducing Anxiety Before Childbirth in Third Trimester Primigravida: A Quantitative Study in Indonesia - Noorlinda, Noorlinda; Sartika, Sartika (Journal of Current Health Sciences, 2025)
Pre-labor anxiety is common among third trimester primigravida women and is linked to negative maternal and neonatal outcomes. This study examined the effect of hypnobirthing on anxiety levels in primigravida women at Karangnunggal Public Health Center, Tasikmalaya Regency, Indonesia. Using a one-group pretest-posttest design, 21 eligible participants (aged 18–35 years, ≥28 weeks gestation) received a standardized hypnobirthing intervention over four sessions in eight days. Maternal anxiety was assessed before and after the intervention with the validated Hamilton Anxiety Rating Scale (HARS). Mean anxiety scores decreased significantly from 3.52 (SD = 1.03) to 1.52 (SD = 0.68) (p = 0.025), with a large effect size (Cohen’s d = 2.29). The proportion with severe or very severe anxiety dropped from 66.6% to 0%, while those reporting no anxiety rose from 4.8% to 57.1%. These results demonstrate the effectiveness of hypnobirthing as a non-pharmacological intervention for reducing pre-labor anxiety and support its integration into antenatal care. The study provides novel evidence in the Indonesian context and highlights the value of psychological interventions to enhance maternal well-being and birth experiences. Further research with larger, controlled samples is recommended. Abstrak: Kecemasan pra-persalinan umum terjadi pada ibu hamil primigravida trimester ketiga dan berhubungan dengan dampak negatif bagi ibu maupun bayi. Penelitian ini menelaah pengaruh hypnobirthing terhadap tingkat kecemasan pada ibu hamil primigravida di Puskesmas Karangnunggal, Kabupaten Tasikmalaya, Indonesia. Dengan desain pretest-posttest satu kelompok, sebanyak 21 partisipan yang memenuhi syarat (usia 18–35 tahun, usia kehamilan ≥28 minggu) mengikuti intervensi hypnobirthing terstandar selama empat sesi dalam delapan hari. Kecemasan ibu diukur sebelum dan sesudah intervensi menggunakan Hamilton Anxiety Rating Scale (HARS) yang telah divalidasi. Rata-rata skor kecemasan menurun secara signifikan dari 3,52 (SD = 1,03) menjadi 1,52 (SD = 0,68) (p = 0,025), dengan effect size besar (Cohen’s d = 2,29). Proporsi ibu dengan kecemasan berat atau sangat berat menurun dari 66,6% menjadi 0%, sedangkan yang tidak mengalami kecemasan meningkat dari 4,8% menjadi 57,1%. Hasil ini menunjukkan efektivitas hypnobirthing sebagai intervensi non-farmakologis untuk menurunkan kecemasan pra-persalinan dan mendukung integrasinya dalam perawatan antenatal. Studi ini memberikan bukti baru dalam konteks Indonesia dan menyoroti pentingnya intervensi psikologis untuk meningkatkan kesejahteraan ibu dan pengalaman persalinan. Penelitian lanjutan dengan sampel lebih besar dan desain terkontrol sangat dianjurkan.